PROBLEMS AND PROSPECTS OF THE PRODUCTION OF GLUTEN-FREE BAKERY PRODUCTS IN UKRAINE - Слащева, Аліна; Федорова, Діна; Ланська, Віта (SWorldJournal, 2022)
The paper examines the prospects of creating gluten-free bakery products in Ukraine and the world. The purpose of the article is to identify problems and determine prospects for the production of gluten-free bakery products in Ukraine. It was determined